Alternative splicing of human NT5E in cirrhosis and hepatocellular carcinoma produces a negative regulator of ecto-5′-nucleotidase (CD73) - Snider, Natasha T. (Mol Biol Cell, 2014)
Ecto-5′-nucleotidase (CD73), encoded by NT5E, is the major enzymatic source of extracellular adenosine. CD73 controls numerous pathophysiological responses and is a potential disease target, but its regulation is poorly understood. We examined NT5E regulation by alternative splicing. Genomic database analysis of human transcripts led us to identify NT5E-2, a novel splice variant that was expressed at low abundance in normal human tissues but was significantly up-regulated in cirrhosis and hepatocellular carcinoma (HCC). NT5E-2 encodes a shorter CD73 isoform we named CD73S. The presence of CD73S protein, which lacks 50 amino acids, was detected in HCC using an isoform-specific antibody. A noncanonical mouse mRNA, similar to human CD73S, was observed, but the corresponding protein was undetectable. The two human isoforms exhibited functional differences, such that ectopic expression of canonical CD73 (CD73L) in human HepG2 cells was associated with decreased expression of the proliferation marker Ki67, whereas CD73S expression did not have an effect on Ki67 expression. CD73S was glycosylated, catalytically inactive, unable to dimerize, and complexed intracellularly with the endoplasmic reticulum chaperone calnexin. Furthermore, CD73S complexed with CD73L and promoted proteasome-dependent CD73L degradation. The findings reveal species-specific CD73 regulation, with potential significance to cancer, fibrosis, and other diseases characterized by changes in CD73 expression and function.